Health economics and emergence from COVID-19 lockdown: the great big marginal analysis. Issue 2 (6th April 2022) - Donaldson, Cam; Mitton, Craig
Abstract: Despite denials of politicians and other advisors, trade-offs have already been apparent in many policy decisions addressing the coronavirus disease 2019 pandemic and its social and economic consequences. Here, we illustrate why it is important, from a wellbeing perspective, to recognise such trade-offs, and provide a framework, based on the economic concept of 'marginal analysis', for doing so. We illustrate its potential through consideration of optimising the balance between reducing the reproductive rate ( R ) of the virus and further opening of the economy. The framework accommodates both perspectives in the health-vs-economy debate whereby, depending on where we are within the marginal analysis framework, either health issues are allowed to dominate or, below some threshold of R and/or background level of infection, health and economic considerations can be traded off against each other. Given the inevitability of such trade-offs, the framework exposes crucial questions to be addressed, such as: the critical value of R and/or background infection, above which health considerations predominate, and which may vary from jurisdiction to jurisdiction; and the value of lives forgone resulting from the small increases in R and/or background infection levels that may have to be tolerated as the economy is gradually opened.